2021
DOI: 10.1002/bab.2191
|View full text |Cite
|
Sign up to set email alerts
|

Simple colorimetric screening of paraquat residue in vegetables evaluated by localized surface plasmon resonance of gold nanoparticles

Abstract: The contamination of paraquat in vegetables is widely connected with human health risks, leading to the research interest in developing a paraquat sensing system. This work reports a simple detection method of paraquat based on the electrostatic interaction of paraquat and the negatively charged gold nanoparticles (AuNPs), resulting in the changes of colors from red to blue and the shifting of localized surface plasmon resonance (LSPR) peaks of AuNPs. The limit of detection concentration (C LOD ) of this syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although this method showed high sensitivity and selectivity for paraquat detection, it required complex pretreatment steps and complicated data analysis. Later, several simple biosensors for paraquat detection were reported, and their principles were based on the interaction between the positively charged paraquat and negatively charged AuNPs such as 3‐mercapto‐1‐propanesulfonate (3MPS)‐capped AuNPs and citrate‐capped AuNPs 25,26 . For 3MPS, the SO 3 − groups of 3MPS provide the negatively charged surface of AuNPs, which can interact with the positive charges of nitrogen atoms at pyridine rings of paraquat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this method showed high sensitivity and selectivity for paraquat detection, it required complex pretreatment steps and complicated data analysis. Later, several simple biosensors for paraquat detection were reported, and their principles were based on the interaction between the positively charged paraquat and negatively charged AuNPs such as 3‐mercapto‐1‐propanesulfonate (3MPS)‐capped AuNPs and citrate‐capped AuNPs 25,26 . For 3MPS, the SO 3 − groups of 3MPS provide the negatively charged surface of AuNPs, which can interact with the positive charges of nitrogen atoms at pyridine rings of paraquat.…”
Section: Introductionmentioning
confidence: 99%
“…Later, several simple biosensors for paraquat detection were reported, and their principles were based on the interaction between the positively charged paraquat and negatively charged AuNPs such as 3mercapto-1-propanesulfonate (3MPS)-capped AuNPs and citrate-capped AuNPs. 25,26 For 3MPS, the SO 3 − groups of 3MPS provide the negatively charged surface of AuNPs, which can interact with the positive charges of nitrogen atoms at pyridine rings of paraquat. Via this electrostatic interaction, paraquat can induce the aggregation of 3MPS-capped AuNPs, resulting in the color changes from red to blue.…”
mentioning
confidence: 99%
“…found that AuNPs aggregate and precipitate in saline solutions below the NaCl concentration of many bodily fluids and blood plasma. Siri et al [10c] . built AuNPs method for detecting paraquat, NaCl was selective to enhance the detection sensitivity of the system.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to its chemical stability and solubility in water, PQ can easily accumulate in the environment and in agricultural products, and then enter the human body via food chain. PQ contamination in agricultural products is one of the highly concerning food safety issues in many countries [ 9 ]. It has been reported that PQ was detected in various food products including cabbage, guava, eggplant and round gourd [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%